Dental malformations associated with biallelic MMP20 mutations. Issue 8 (3rd June 2020) - Wang, Shih‐Kai; Zhang, Hong; Chavez, Michael B.; Hu, Yuanyuan; Seymen, Figen; Koruyucu, Mine; Kasimoglu, Yelda; Colvin, Connor D.; Kolli, Tamara N.; Tan, Michelle H.; Wang, Yin‐Lin; Lu, Pei‐Ying; et al.
Abstract: Background: Matrix metallopeptidase 20 (MMP20) is an evolutionarily conserved protease that is essential for processing enamel matrix proteins during dental enamel formation. MMP20 mutations cause human autosomal recessive pigmented hypomaturation‐type amelogenesis imperfecta (AI2A2; OMIM #612529). MMP20 is expressed in both odontoblasts and ameloblasts, but its function during dentinogenesis is unclear. Methods: We characterized 10 AI kindreds with MMP20 defects, characterized human third molars and/or Mmp20 −/− mice by histology, Backscattered Scanning Electron Microscopy (bSEM), µCT, and nanohardness testing. Results: We identified six novel MMP20 disease‐causing mutations. Four pathogenic variants were associated with exons encoding the MMP20 hemopexin‐like (PEX) domain, suggesting a necessary regulatory function. Mutant human enamel hardness was softest (13% of normal) midway between the dentinoenamel junction (DEJ) and the enamel surface. bSEM and µCT analyses of the third molars revealed reduced mineral density in both enamel and dentin. Dentin close to the DEJ showed an average hardness number 62%–69% of control. Characterization of Mmp20 −/− mouse dentin revealed a significant reduction in dentin thickness and mineral density and a transient increase in predentin thickness, indicating disturbances in dentin matrix secretion and mineralization. Conclusion: These results expand the spectrum of MMP20 disease‐causing mutations and provide the first evidence for MMP20 function during dentin formation. Abstract : Matrix metallopeptidase 20 (MMP20) is specifically expressed by ameloblasts during enamel formation and by odontoblasts during dentin formation. Here we characterized 10 kindreds with MMP20 defects and identified 6 novel disease‐causing mutations. Hardness testing of third molars from a patient with biallelic MMP20 p.Ala304Gly defects showed enamel that was only 48‐61% as hard as controls, with the softest enamel midway between the dentinoenamel junction (DEJ) and the enamel surface. Human mutant dentin close to the DEJ showed average hardness numbers 62‐69% of control, indicating a hardness defect in the superficial dentin. Dentin further away from the DEJ showed normal hardness.